Impacts of Artificial Intelligence on Employment: Universal Basic Income as a Social Policy Measure - Gökhan Murat; Belemir Şengül (Sosyal Siyaset Konferansları Dergisi)
Developments in artificial intelligence and robotics technology in the last 20 years have highlighted the possibility of substitution between technology and labor. As artificial intelligence and autonomous robots are increasingly integrated into working life, tasks undertaken by machines are also increasing. The role of the labor factor in working life and its proportion in national income are decreasing. Hence, this study aims to examine the development process of artificial intelligence and autonomous robots and their impact on employment. The feasibility of universal basic income as a social policy measure is investigated to address the possible negative effects of artificial intelligence and autonomous robots on employment. The context development, advantages, and objections of universal basic income are examined, and its importance as a social policy tool is mentioned. Consequently, results show that in the long term, artificial intelligence and autonomous robots will force the transformation of jobs, with many jobs being performed by robots with artificial intelligence. Universal basic income can be adopted globally as a social policy measure to ensure the balance of production and consumption and increase demand for goods and services.